Exercise 7.2.2

Exercise statement

Prove Proposition 7.2.5.

Proposition 7.2.5. Let \sum_{n=m}^\infty a_n be a formal series of real numbers. Then \sum_{n=m}^\infty a_n converges if and only if, for every real number \varepsilon > 0, there exists an integer N \geq m such that

\displaystyle \left|\sum_{n=p}^q a_n\right| \leq \varepsilon for all p,q \geq N.

Hints

  1. Use Proposition 6.1.12 and Theorem 6.4.18.
  2. If you want to do this exercise correctly, it is not as easy as just applying the given Proposition and/or Theorem!

How to think about the exercise

If you look up the hints, it is quite obvious how the exercise is done. I wanted to give a thought process of how to approach the problem if one randomly saw it (i.e. without accompanying hints), so in what follows I won’t be assuming that the hints have been given.

Let’s write out the two sides of the “if and only if” by making the quantifiers explicit:

For all \varepsilon > 0 there exists N \geq m such that for all p,q \geq N we have \left|\sum_{n=p}^q a_n\right| \leq \varepsilon           (1)

The claim that \sum_{n=m}^\infty a_n converges is:

For all \varepsilon > 0 there exists N \geq m such that for all k \geq N we have \left|\sum_{n=m}^k a_n - S\right| \leq \varepsilon           (2)

Above, I have used S to denote the sum. It’s actually equal to S=\sum_{n=m}^\infty a_n.

This shows something interesting. When formalizing what it meant for a series to converge, i.e., when writing out (2), we had to refer to what the sum converges to, i.e., to S. But in (1), we did not even have to refer to the final sum! In other words, (1) encodes the claim “this series converges” without talking about what the series converges to. This sounds awfully familiar … didn’t we have a way to say “this sequence converges” without referring to the limit of the sequence? That’s right, this is sounding exactly like what Cauchy sequences are. And in fact, if our pattern-matching is active, we might even notice that in (1) we had “for all p,q \geq N” which is reminiscent of the “for all j,k \geq N” that we used a lot when dealing with Cauchy sequences (the variable names don’t matter of course).

So let’s see … if S_N = \sum_{n=m}^N a_n is the Nth partial sum of the series, then \sum_{n=p}^q a_n is basically equal to S_q - S_p. (How did I see this? It was so quick it’s hard for me to say what my mind did here. I suppose it’s pattern-matching on things I’ve seen before, e.g. the integral rule \int_a^b + \int_b^c = \int_a^c, which can be written in subtracted form as \int_a^c - \int_a^b =\int_b^c.) So \left|\sum_{n=p}^q a_n\right| \leq \varepsilon is basically saying |S_q - S_p| \leq \varepsilon. So (1) is basically saying that (S_N)_{N=m}^\infty is Cauchy. And we have exactly the theorems to show that “is Cauchy” and “is convergent” are the same for sequences.

I said “basically” above because \sum_{n=p}^q a_n = S_q - S_p only holds when q \geq p. When q < p, the sum \sum_{n=p}^q a_n = 0 whereas S_q - S_p is not necessarily zero; instead it’s equal to -\sum_{n=q+1}^p a_n. And actually, I’ve made an off-by-one error: \sum_{n=p}^q a_n should actually be S_q - S_{p-1}. So this exercise is perhaps not as simple we thought! The first challenge was to figure out the “big idea” or strategy to use (i.e., recognize that Cauchyness is relevant), and the second challenge is now to make our idea actually work by getting all of the details right. Let’s write out all the variations of the claims we are working with, to get things straight:

(S_N)_{N=m}^\infty is Cauchy           (a)

For all \varepsilon > 0 there exists N \geq m such that for all p,q \geq N we have |S_q - S_p| \leq \varepsilon           (b)

For all \varepsilon > 0 there exists N \geq m such that for all p,q \geq N we have |S_q - S_{p-1}| \leq \varepsilon           (c)

For all \varepsilon > 0 there exists N \geq m such that for all p,q \geq N we have \left|\sum_{n=p}^q a_n\right| \leq \varepsilon           (d)

Our goal is to show that (a) and (d) are the same (why do we want to show both directions? It’s because the original Proposition is stated as an “if and only if”). That will allow us to use the fact that a sequence is Cauchy iff it is convergent.

It’s clear that (a) and (b) are equivalent, since (b) is just what it means for a sequence to be Cauchy. So we just need to show that (b) and (c) are equivalent and that (c) and (d) are equivalent.

(c) implies (b) since if |S_q - S_{p-1}| \leq \varepsilon holds for all p,q \geq N, then since p+1 \geq N as well, we have |S_q - S_{(p+1)-1}| \leq \varepsilon, i.e., |S_q - S_p| \leq \varepsilon.

(b) implies (c) since if we have some N such that |S_q - S_p| \leq \varepsilon for all p,q \geq N, then we can pick N+1 and see that if p,q \geq N+1 then p-1,q \geq N and so |S_q - S_{p-1}| \leq \varepsilon.

(The above two paragraphs are similar to Exercise 6.1.3 and Exercise 6.1.4. In all cases, what matters is what happens at the limits so shifting things around a bit won’t change whether a statement is true.)

So now we just have to show that (c) and (d) are equivalent. Being very mindful of off-by-one errors now, if q \geq p we have \sum_{n=p}^q a_n = S_q - S_{p-1}, and if q < p instead we have \sum_{n=p}^q a_n = 0 and

\begin{aligned}S_q - S_{p-1} &= (a_1 + \cdots + a_q) - (a_1 + \cdots + a_q + a_{q+1} + \cdots + a_p) \\ &= -(a_{q+1} + \cdots + a_p) \\ &= -\sum_{n=q+1}^p a_n\end{aligned}

So whatever p,q are, we have \left|\sum_{n=p}^q a_n\right|\leq |S_q - S_{p-1}|. This means (c) implies (d): if the bigger thing is less than \varepsilon, then so is the smaller thing. To show that (d) implies (c) as well, let \varepsilon > 0. Since (d) is true, we have some N; pick this N. Now let p,q \geq N. If q \geq p, we have \sum_{n=p}^q a_n = S_q - S_{p-1} so we have |S_q - S_{p-1}| = \left|\sum_{n=p}^q a_n\right| \leq \varepsilon. If q < p then from (d) we have \left|\sum_{n=q}^p a_n\right| \leq \varepsilon. But we know that S_q - S_{p-1} = -\sum_{n=q+1}^p a_n, so actually we want to show that \left|\sum_{n=q+1}^p a_n\right| \leq \varepsilon. But this is possible since q+1 \geq N. So in other words we have

\displaystyle |S_q - S_{p-1}| = \left|\sum_{n=q+1}^p a_n\right| \leq \varepsilon

That was a lot of fiddly details, but we’re finally done.

Model solution

Let S_N = \sum_{n=m}^N a_n be the Nth partial sum of the series \sum_{n=m}^\infty a_n. By definition of series convergence, \sum_{n=m}^\infty a_n converges iff the sequence (S_N)_{N=m}^\infty converges.

We will show that (S_N)_{N=m}^\infty is Cauchy if and only if, for every \varepsilon > 0 there exists an integer N \geq m such that for all p,q \geq N we have \left|\sum_{n=p}^q a_n \right| \leq \varepsilon. If we can do this, then Theorem 6.4.18 will guarantee the result that we are trying to show.

First suppose that (S_N)_{N=m}^\infty is Cauchy. Let \varepsilon > 0. Since (S_N)_{N=m}^\infty is Cauchy, this means that there exists an integer N \geq m such that for all p,q \geq N we have |S_q - S_p| \leq \varepsilon.  Consider the number N+1. If p,q \geq N+1, then q, p-1 \geq N. Now we have two cases. If q \geq p, then the sum \sum_{n=p}^q a_n is equal to S_q - S_{p-1} (Lemma 7.1.4(a)), so we have \left|\sum_{n=p}^q a_n\right| = |S_q - S_{p-1}| \leq \varepsilon by Cauchyness. If on the other hand q < p, then \left|\sum_{n=p}^q a_n\right| = 0 < \varepsilon (Definition 7.1.1). Let us summarize: we let \varepsilon > 0, then found a number N+1 \geq m such that if p,q \geq N+1 then \left|\sum_{n=p}^q a_n\right| \leq \varepsilon. So we’ve completed the first direction of the proof.

Now suppose that for every \varepsilon > 0 there exists an integer N \geq m such that for all p,q \geq N we have \left|\sum_{n=p}^q a_n \right| \leq \varepsilon. Let \varepsilon > 0. From our assumption, we are given some N \geq m, so pick this N. Now let p,q \geq N. We have \left|\sum_{n=p}^q a_n \right| \leq \varepsilon, and we want to show |S_q - S_p| \leq \varepsilon. We have three cases:

  • If q=p then |S_q - S_p| = 0 < \varepsilon.
  • Next, if q > p then q \geq p+1 and we have \sum_{n=p+1}^q a_n = S_q - S_p by Lemma 7.1.4(a). And since q,p+1 \geq N we can say that \left|\sum_{n=p+1}^q a_n \right| \leq \varepsilon. But this means |S_q - S_p| \leq \varepsilon as required.
  • Finally, if q < p then q+1 \leq p and we have S_q - S_p = -(S_p - S_q) = -\sum_{n=q+1}^p a_n. But since q+1, p \geq N we have \left|\sum_{n=q+1}^p a_n\right| \leq \varepsilon, so |S_q - S_p| = |S_p - S_q| = \left|\sum_{n=q+1}^p a_n\right| \leq \varepsilon as required.

In all three cases we have shown that |S_q - S_p| \leq \varepsilon so we are done.

Exercise 6.6.4

Exercise statement

Prove Proposition 6.6.5. (Note that one of the two implications has a very short proof.)

Proposition 6.6.5 (Subsequences related to limits). Let (a_n)_{n=0}^\infty be a sequence of real numbers, and let L be a real number. Then the following two statements are logically equivalent (each one implies the other):

(a) The sequence (a_n)_{n=0}^\infty converges to L.
(b) Every subsequence of (a_n)_{n=0}^\infty converges to L.

Hints

  1. For one of the directions, use Lemma 6.6.4.

How to think about the exercise

This is a pretty straightforward exercise. I could leave it at that, but I want to try something new. So here’s a kind of stream-of-consciousness account of how I approached the problem:

We want to show (a) and (b) are the same. So first suppose (a) is true. We want to show (b) is true. What does that mean? Let’s unwrap:

Let (a_n)_{n=0}^\infty be a sequence of real numbers, and suppose (a_n)_{n=0}^\infty converges to L \in \mathbf R. Now we want to show that every subsequence of (a_n)_{n=0}^\infty converges to L. It would be good to have an arbitrary subsequence and to give it a name. So let (b_n)_{n=0}^\infty be a subsequence of (a_n)_{n=0}^\infty. What does this mean? By definition, this means that there is a strictly increasing function f : \mathbf N \to \mathbf N such that b_n = a_{f(n)} for all n \in \mathbf N.

Now, we want to show that (b_n)_{n=0}^\infty converges to L. How do we do that? To show that any sequence converges at all, the usual thing to do is to let \varepsilon > 0 be arbitrary. Now we have to find some N such that n \geq N implies |b_n - L| \leq \varepsilon. How do we find such an N? The only possible way is to use some fact about (a_n)_{n=0}^\infty, because that’s the only sequence we know anything about. We know that (a_n)_{n=0}^\infty converges to L. That means that for any \varepsilon > 0 (including the one we defined earlier), there is N such that n \geq N implies |a_n - L| \leq \varepsilon. Okay, that is pretty close to what we want. Since we don’t know any other N to use, let’s just pick this N that we know exists, for now. We know that:

if n \geq N then |a_n - L|\leq \varepsilon. (*)

We want to show that:

if n \geq N then |b_n - L|\leq \varepsilon;

or, making the relation between (a_n)_{n=0}^\infty and (b_n)_{n=0}^\infty clear, we want to show that:

if n \geq N then |a_{f(n)} - L|\leq \varepsilon.

So in other words, assuming n \geq N, we have |a_n - L|\leq \varepsilon and we want |a_{f(n)} - L|\leq \varepsilon. Can we get what we want? We could if we knew that f(n) \geq N (because of (*)). In other words, we want to know if n \geq N implies f(n) \geq N. One way this could be true is if f(n) \geq n, so that f(n) \geq n \geq N. (Here I have “cheated” a bit. I have seen the pattern “f(n) \geq n” many times before, so it was immediately obvious to me that I should use it. I tried to give an account of how one might have reached the same conclusion without having known the pattern ahead of time, but I don’t know if I’ve succeeded.) This seems pretty plausibly true. The identity function seems like the slowest-growing strictly increasing function (it just counts up one by one), but other strictly increasing functions can be faster-growing (they can skip some numbers). It seems like an easy case of induction. It’s clear that f(0) \geq 0, and if f(n) \geq n then since f(n+1) > f(n), we have f(n+1) > n, so f(n+1) \geq n+1. So that completes the proof that (a) implies (b).

Now we do the other direction. Suppose every subsequence of (a_n)_{n=0}^\infty converges to L. We want to show that (a_n)_{n=0}^\infty converges to L. Since we know something about every subsequence, it seems like we ought to pick some clever particular subsequence to get what we want – oh, we can just pick (a_n)_{n=0}^\infty to be the subsequence!

Model solution

First we show that (a) implies (b). Suppose the sequence (a_n)_{n=0}^\infty converges to L. We want to show that every subsequence of (a_n)_{n=0}^\infty converges to L. So let (b_n)_{n=0}^\infty be a subsequence of (a_n)_{n=0}^\infty. This means there is some strictly increasing function f : \mathbf N \to \mathbf N such that b_n = a_{f(n)} for all n \in \mathbf N. We will show that (b_n)_{n=0}^\infty converges to L. Let \varepsilon > 0. Since (a_n)_{n=0}^\infty converges to L, there exists some N \geq 0 such that:

  • for all n\geq N we have |a_n - L| \leq \varepsilon. (*)

Pick this N, and let n \geq N. We want to show that |b_n - L| \leq \varepsilon. If we can show that f(n) \geq n for all n \in \mathbf N, then we would have f(n) \geq n \geq N, so by (*) we have |a_{f(n)} - L| \leq \varepsilon. By definition of (b_n)_{n=0}^\infty this means we have |b_n - L| \leq \varepsilon as required.

So it remains to show that f(n) \geq n for all n \in \mathbf N. We proceed by induction. The base case f(0) \geq 0 follows since the range of f is \mathbf N. Now suppose inductively that f(n) \geq n. Since f is strictly increasing, we have f(n+1) > f(n). Thus we have f(n+1) > n. By Proposition 2.2.12(e) we have f(n+1) \geq n+1 as required. This closes the induction.

Next we show that (b) implies (a). This follows immediately from Lemma 6.6.4: (a_n)_{n=0}^\infty is a subsequence of itself, so if every subsequence of (a_n)_{n=0}^\infty converges to L then in particular (a_n)_{n=0}^\infty must converge to L.